(untitled) (Historical Studies on Central Europe, 2023)
The main goal of Historical Studies on Central Europe is to provide an interdisciplinary and international platform for disseminating new findings on Central Europe and enhancing the dialog on it. In this spirit, the editors have decided to launch a series asking prominent scholars of the region: their personal motivations for choosing Central Europe as their field; their view on central questions of methodology, trends, and definition, as well as their opinion on the status of the field. Miroslav Hroch is professor emeritus at Charles University (Prague), where he founded a Seminar in Comparative History in 1994. He wrote pioneering comparative works on the question of nation formation, most notably Social Preconditions of National Revival in Europe (1985; originally published in German in 1968). With his comparative researches on national movements, Professor Hroch earned international recognition, in 1997 he received an honorary doctorate from Uppsala University, Sweden. His other significant books include In the National Interest. Demands and Goals of European National Movements of the Nineteenth Century: a Comparative Perspective (2000); European Nations. Explaining their Formation (2015, originally published in German in 2005).